PELATIHAN PEMBUKUAN SEDERHANA BAGI PELAKU UMKM PENGOLAHAN HASIL LAUT DI KELURAHAN KOLO KOTA BIMA - Aliah Pratiwi; Nurul Huda; Nafisah Nurulrahmatiah; M. Rimawan (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
MSMEs are one of the sectors that support economic growth in Indonesia. The MSME sector must be able to provide its financial reports. This community service was carried out in Kolo Village, Bima City, NTB, one of the areas where MSMEs have not been able to fully keep simple bookkeeping. The purpose of the Community Service (PKM) activity entitled Simple Bookkeeping Training for Micro, Small and Medium Enterprises (MSMEs) processing seafood in the Kolo Sub-District, Kota Bima is so that the people in Kolo Sub-District, Kota Bima, where the majority are MSME actors, are able to make simple bookkeeping of financial transactions. owned so that receipts, expenses and profits (profits) or losses obtained can be measured and controlled to determine the progress of their business from time to time. The method used is training on simple bookkeeping by using the Cash Receipt and Disbursement Book for all MSME operational activities. The Simple Bookkeeping Training for MSMEs in the Kolo Village, Kota Bima, received a positive response. Outcome of Community Service activities This community (PKM) is MSME actors who are able to keep books of their business on a regular basis using the Cash Receipt and Expenditure Book and calculate profits (profits) or losses correctly.